IMPLIKASI DIGITAL READINESS SI ICE MANDIRI DALAM PELAYANAN PERIZINAN BERUSAHA TERINTEGRASI OSS DI MALL PELAYANAN PUBLIK (STUDI KASUS MALPRAKTIK ADMINISTRATIF DI SUMEDANG) - Atien Nurbaeti (JRPA - Journal of Regional Public Administration, 2026)
This study aims to analyze the implications of digital readiness of the Independent Permit Printing Information System (SI ICE Mandiri) in integrated business licensing services with the Online Single Submission (OSS) system, and to evaluate actions taken regarding administrative malpractice errors at the Public Service Mall in Sumedang Regency. Using a qualitative approach and descriptive method, data were collected through observation, in-depth interviews with DPMPTSP officers, and documentation of regulations and internal reports. The findings reveal that although technical infrastructure and human resources are adequate, low digital literacy among MSME applicants and rural communities remains the primary barrier to system effectiveness. Furthermore, user input errors and insufficient guidance have led to administrative malpractices such as duplicated processes and document discrepancies. Although SI ICE Mandiri is designed to enhance transparency and efficiency, without intensive socialization and training interventions, its potential cannot be maximized. This study recommends strengthening community digital capacity through tiered training programs and optimizing the role of officers as on-the-ground technology facilitators.